Assessing the appropriateness of lumbar spine MRI referrals in low back pain management: a tertiary care hospital study - Sana, Sana; Sachdev, Namrita (International Journal of Research in Medical Sciences, 2025)
Background: Low back pain (LBP) is a leading cause of disability globally, yet most cases are nonspecific, with no clear pathology. The routine use of MRI for diagnosing LBP is debated, as overuse may lead to unnecessary procedures, increased healthcare costs, and patient anxiety. This study aimed to evaluate adherence to the American College of Radiology (ACR) appropriateness criteria for lumbar spine MRI referrals at a tertiary care hospital. Methods: A retrospective study analysed 200 lumbar spine MRI referrals from January to June 2022. Referrals were reviewed for appropriateness based on ACR guidelines. Data included patient demographics, referring specialties, and clinical indications. Referrals were classified as appropriate or inappropriate, with trends across specialties identified. Results: Of the 200 referrals, 71% (142) were deemed appropriate, primarily for cases with red flags or persistent neurological symptoms. 29% (58) were inappropriate, often involving acute back pain without red flags or failed conservative management. General practitioners and emergency medicine specialists had the highest rates of inappropriate referrals (43.5% and 37.2%, respectively), while orthopedics and neurosurgery showed more adherence to guidelines. Conclusions: This study highlights the need for improved adherence to the ACR appropriateness criteria in MRI referrals for LBP. Overuse of MRI contributes to unnecessary healthcare costs and patient risk. Enhancing clinician education, documentation practices, and decision support tools could reduce inappropriate MRI use, improving patient care and reducing costs.